2005
DOI: 10.1007/s10633-005-7345-x
|View full text |Cite
|
Sign up to set email alerts
|

The Photopic ERG of the Albino Guinea Pig (Cavia porcellus): A Model of the Human Photopic ERG

Abstract: Altricial rodents such as rats and mice are probably the most widely used animal model in the electroretinogram (ERG) literature. However, while the scotopic responses of these rodents share obvious similarities with that of humans, their photopic electroretinograms are strikingly different. For instance, the photopic ERGs of rats and mice include, when measurable, a minimal a-wave, while the b-wave is of much larger amplitude than that of humans. The purpose of this study is to present the albino guinea pig w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
2
11
0
2
Order By: Relevance
“…Our results are in line with previous studies also reporting a postnatal maturation of the photopic ERG in human infants [26,27,29,41]. Given our previous demonstration [55] of significant morphological and functional similarities between the photopic ERGs of guinea pigs and human, our results could also suggest that, compared to other rodents such as rats or mice, the newborn guinea pigs could represent a better animal model to study the normal postnatal retinal maturation in the human infant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with previous studies also reporting a postnatal maturation of the photopic ERG in human infants [26,27,29,41]. Given our previous demonstration [55] of significant morphological and functional similarities between the photopic ERGs of guinea pigs and human, our results could also suggest that, compared to other rodents such as rats or mice, the newborn guinea pigs could represent a better animal model to study the normal postnatal retinal maturation in the human infant.…”
Section: Discussionsupporting
confidence: 92%
“…However, these age-dependent changes are closer in magnitude to what is reported for humans or primates compared to what is reported for animals born with a more immature visual system such as rodents (mice and rats). Given that the ERG of albino guinea pigs, especially the photopic ERG, was also previously shown to share features common to the human cone ERG [55], we believe that it should be considered as a valid alternative whenever an animal model of the human ERG is considered.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported ERG differences in animal models based on fundus pigmentation levels [22][23][24][25][26][27][28], and others have compared human participants [2-6, 29, 30]. Our findings that some ERGs are larger from those with lighter eyes are in keeping with previous studies [2][3][4][5][6][7].…”
Section: Discussionsupporting
confidence: 91%
“…For the light-adapted OPs, very marked amplitude differences (blue [ brown) were noted for OP4 (P \ 0.0001) and OP5 (P = 0.001). These later OPs are also particularly associated with the OFF retinal pathway [27,38,39]. Those aspects of the light-adapted ERG associated with ON retinal pathways, the saturated b-wave amplitude (as described by the logistic growth component of the photopic hill model) and the earlier OPs, showed no difference between blue and brown eyes.…”
Section: Discussionmentioning
confidence: 91%
“…10,11,13 The flash electroretinography (ERG) is one method of evaluating the integrity to the neural circuitry, and it is a diffuse response from the whole retina and is thus sensitive to widespread diseases of the retina. It has been found that the guinea pig has electroretinographic patterns similar to humans and primates, 14,15 but the effects of disruption of the diurnal light/dark cycles on retinal function and eye growth have not been studied in as much detail in guinea pig. Therefore, in the current research, we measured refractive errors and ocular dimensions as a function of the temporal modulation of animals and flicker parameters in developing guinea pigs.…”
Section: Introductionmentioning
confidence: 99%